Strengthening Moral Education Values: Sociological Analysis of the Mbah Sholeh Haolan at Pesantren Benda Kerep, Cirebon - Rusmana, Dadan; Rosidin, Didin Nurul; Saefullah, Asep; Burhanudin, Dede; bin Zainuddin, Ghazali (Universitas Islam Negeri Mataram, 2024)
This article explores the role of Mbah Sholeh haolan (commemoration) in strengthening Islamic education in Benda Kerep Village. This event serves as a cornerstone for cultural preservation, intergenerational learning, and practical implementation of Islamic values. The kyai, or spiritual leaders, play a pivotal role in guiding the community, reinforcing their authority and the respect they command. The haolan facilitates social cohesion, fosters a strong sense of identity, and exemplifies the community’s commitment to Islamic teachings. By examining the significance of Mbah Sholeh haolan, the article provides insights into how traditional Islamic communities can navigate the challenges of modernity while preserving their religious and cultural heritage. This study show that commemoration is one of the means used to pass on the cultural and religious values contained in